Speech text of signing ceremony memorandum of understanding (MoU) between Universiti Teknologi MARA and Universitas Jenderal Achmad Yani Indonesia / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
Alhamdulillah, praise be to Allah S.W.T. for it is with His blessings that we are able to gather this morning at the Memorandum of Understanding (MoU) Signing Ceremony between Universiti Teknologi MARA (UiTM) and Universitas Jenderal Achmad Yani (Unjani), Indonesia. 2. Congratulations to the UiTM Faculty of Medicine for organising this event to pioneer the collaboration of expertise through numerous programmes between the two universities such as conferences, joint research, publications, sharing sessions, and many more.